(untitled) (Journal of the College of Basic Education, 2023)
The areas where the land pressures the sea water strongly are known as straits.which is in the end a contraction of sea water confined betweentwo parts of the dry land. In other words, the strait is a sea passage separating two parts.from land and connects two bodies of water (1). Hence, the areas in which it increasesLand pressure on sea water often represents a prominent place in the field of marine strategy.These areas are known as choke points.(2) (Choke Poits). Searching for suffocation in the southern part of the Red Sea.It will make the mind divert directly to the Mandeb Gate as it is a strait to which the adjective fully applies.suffocation. The Bab al-Mandab Strait is a unique strategic location, as it is the southern gateway to the sea.Red and the neck of the bottle that connects it to the Gulf of Aden and from there to the Arabian Sea and the Indian Ocean and thento Southeast and East Asia on the Pacific Ocean as it is the waterway that connects betweenPacific and Indian Oceans and the Mediterranean Sea through the southern entrance to the Red Sea throughthe Suez Canal in the Atlantic Ocean. All the Arabian seas and gulfs would have been linked to this.They converged with the navigable seas and oceans all over the globe. And whatThe Bab al-Mandab Strait is more important because it controls international trade routes for the passage of oil tankers fromThrough it, the region gained vital, strategic and economic importance throughout the ages.